Ethics and pre-exposure prophylaxis (PrEP) in adolescents: an integrative review - Soares, Flávia Moreira; Hellmann, Fernando (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Worldwide estimates suggest an increase in the number of deaths by AIDS among adolescents. The Pre-Exposure Prophylaxis (PrEP) has been considered a potential intervention of major impact on new HIV infections. However, the discussion on PrEP in the adolescent population needs to expand mainly regarding ethical issues that emerge with its implementation. Objective: The objective of this research was to identify ethical issues related to PrEP in adolescents in the current scientific literature and discuss their impact in the implementation of this preventive strategy. Methods: An integrative review of the literature was performed on Medline, Scopus, and Web of Science databases using descriptors Ethic and PrEP. Results: The search retrieved 284 articles, of which 16 was related to adolescents and were kept in the sample after analysis. The issues detected were classified into two categories: 1) Ethics in research and 2) Ethical problems regarding access to PrEP. Conclusion: It seems that the issues discussed could diminish the potential impact of PrEP on new HIV infections among adolescents. Discussions on the theme must be deepened, as gaps regarding Ethics and HIV prevention in adolescents are evident, especially when it comes to sexual minorities, both in research and assistance.